2017
DOI: 10.1080/01904167.2017.1381728
|View full text |Cite
|
Sign up to set email alerts
|

Response of a wild-type and modern cowpea cultivars to arbuscular mycorrhizal inoculation in sterilized and non-sterilized soil

Abstract: Cowpea is an important crop that serves as a legume and vegetable source to many smallholder farmers in sub-Saharan Africa. Soil fertility is a significant limitation to its production thus; inoculation with beneficial soil biota such as arbuscular mycorrhizal fungi (AMF) could improve its performance. However, plant-AMF interaction could vary based on crop cultivar hence affecting overall crop production. The present study aimed at determining the effect of AMF inoculation and soil sterilization on root colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
4
18
0
1
Order By: Relevance
“…Consequently, plants adjust belowground C allocation contributing to the formation of a shorter mycorrhizal root system (Jacobsen, Smith, & Smith, ), relying on the fungal mycelium for nutrient uptake (Smith, ). In fact, there was a significant enhancement in shoot nutrient content (Table ), particularly N and P, which has also been described in other studies with inoculated cowpea (Boby, Balakrishna, & Bagyaraj, ; Oruru et al., ; Sanginga, Lyasse, & Singh, ; Yaseen, Burni, & Hussain, ). Still, this enhancement in nutrient content was not enough to result in greater yields, fact perhaps associated with the sink of carbohydrates of the fungal mycelium that the plant could not allocate to seed development and filling.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consequently, plants adjust belowground C allocation contributing to the formation of a shorter mycorrhizal root system (Jacobsen, Smith, & Smith, ), relying on the fungal mycelium for nutrient uptake (Smith, ). In fact, there was a significant enhancement in shoot nutrient content (Table ), particularly N and P, which has also been described in other studies with inoculated cowpea (Boby, Balakrishna, & Bagyaraj, ; Oruru et al., ; Sanginga, Lyasse, & Singh, ; Yaseen, Burni, & Hussain, ). Still, this enhancement in nutrient content was not enough to result in greater yields, fact perhaps associated with the sink of carbohydrates of the fungal mycelium that the plant could not allocate to seed development and filling.…”
Section: Discussionsupporting
confidence: 81%
“…to the formation of a shorter mycorrhizal root system (Jacobsen, Smith, & Smith, 2002), relying on the fungal mycelium for nutrient uptake (Smith, 2000). In fact, there was a significant enhancement in shoot nutrient content (Table 2), particularly N and P, which has also been described in other studies with inoculated cowpea (Boby, Balakrishna, & Bagyaraj, 2008;Oruru et al, 2018;Sanginga, Lyasse, & Singh, 2000;Yaseen, Burni, & Hussain, 2011 and establishment increases the opportunity of seedlings to achieve a positive C and nutrient balance, which is crucial, especially under stress conditions (de Albuquerque & de Carvalho, 2003). Further studies are, therefore, needed to improve this limitation on the germination of cowpea seeds coated with AM fungi.…”
Section: Consequently Plants Adjust Belowground C Allocation Contribsupporting
confidence: 56%
See 1 more Smart Citation
“…However, the evidence that plant selection reduces the ability of crop plants to respond to the AM symbiosis is rather thin (Lehmann et al 2012 and references therein). Differences in plant D r a f t susceptibility to the AM symbiosis was found in many crop plants, such as tomato (Steinkellner et al 2012), cowpea (Oruru et al 2018), and durum wheat (Singh et al 2012), but this variation did not support the hypothesis of a negative effect of plant breeding on the AM symbiosis.…”
Section: Transcendmentioning
confidence: 85%
“…Previous greenhouse studies reported benefits from AM fungi and PGPR, either inoculated by the conventional method (direct application in the soil) or through seed coating in cowpea performance. Nevertheless, there is still lack of information on the effect of AM fungi and PGPR, which can represent a significant barrier to up‐scale microbial applications .…”
Section: Discussionmentioning
confidence: 99%